Comparison of Omeprazole with Ranitidine for Treatment of Symptoms Associated with Gastroesophageal Reflux Disease and Uncomplicated Duodenal Ulcer. (1st June 1996) - Archambault, Andre P; Hunt, Richard H; Cleator, IGM; Sutherland, Lloyd R; Thomson, Alan Br; Williams, C Noel; Taylor, D Wayne; Drysdale, Ann M
Abstract : This randomized, single-blind, parallel group study was conducted to compare omeprazole with ranitidine for the treatment of symptoms associated with gastroesophageal reflux disease (GERD), uncomplicated duodenal ulcer (DU) or both. After baseline assessments, patients were randomized to receive daily treatment with either 20 mg omeprazole or 300 mg ranitidine for four weeks. In total, 1481 patients (1001 omeprazole, 480 ranitidine) with a diagnosis of GERD (n=904) and/or DU (n=577), confirmed by endoscopy or barium meal and reporting moderate to severe symptoms, were included in the analyses. The seventy of overall daytime symptoms reported by the omeprazole group at clinic visits was lower than that reported by the ranitidine group at week 2 for the entire patient group (P=0.0002) and at both weeks 2 and 4 for the subgroup of patients with GERD (P=0.0001 and P=0.001, respectively). The severity of overall night-time symptoms reported by the omeprazole group was lower than that reported by the ranitidine group at week 4 for all patients as a whole (P=0.042) and at both weeks 2 and 4 for the subgroup of patients with GERD (P=0.035 and P=0.010, respectively). There were no significant differences in reports of adverse events. In the omeprazole group, 19% of patients at week 2 and 15% of patients at week 4 reported adverse events, while the corresponding results from the ranitidine group were 21% and 11%. In conclusion, patients with GERD, DU or both treated with omeprazole 20 mg daily for four weeks showed statistically significant reductions in symptoms compared with patients treated with ranitidine 300 mg daily for the same period of time. The percentage of patients with any remaining daytime symptoms was 12% lower in the omeprazole group compared with the ranitidine group at week 2, and 7% lower at week 4. Five per cent fewer patients in the omeprazole group experienced night-time symptoms at either week 2 or week 4.